(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Warfarin, a commonly used oral anticoagulant, is indispensable for preventing thromboembolic disorders. However, due to its narrow therapeutic window and significant interaction potential, overdose poses serious risks of hemorrhage. This paper explores the pharmacodynamics of warfarin, the pathophysiological mechanisms leading to overdose, clinical manifestations, and evidence-based management. Treatment strategies such as Issues related to vitamin K supplementation, PCC, and FFP are considered., along with novel agents. A case series illustrates the practical management and outcomes of warfarin overdose, contributing to clinical understanding and highlighting the need for vigilant monitoring and individualized treatment.